La regulación de los fármacos en las Leyes de Platón - Londoño Sanz, David (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2023)
In the standard manuscript of the Laws the Parisinus Graecus 1807 of the 9th Century AD this dialogue is placed between the Minos and the Epinomis. While in the Minos the pupil refers to the diversity of rites and traditions that can be observed amongst different peoples, the Epinomis stresses the unity of the law. The regulation of symposia, the access to drugs, to intoxicating drinks and to medicine is a fundamental theme of the Laws. This is evident already from the composition of the dialogue, since this theme is discussed in its first books. The art of regulating communal life is shown as a technique that can be perfected through dialogue. Communal drinking can be beneficial, says the anonymous Athenian foreigner, since wine encourages citizens to sing, and through the confrontation with pleasure citizens are able to exercise temperance. Since the consumption of wine may also produce excesses and loss of constraint, its consumption should be regulated. The Athenian proposes a minimal age limit for wine drinking: 18 years old (Laws, 2.666a-e). The position of the Athenian foreigner concerning the regulation of drugs is a message that might be called “antiprohibitionist”, although not in the contemporary sense (individualist and liberal), but in the sense that an absolute prohibition of drug consumption for the citizens is not defended: the proposal is to allow its consumption, but under a legal and communitarian regulation.

En el manuscrito de referencia de las Leyes, el Parisinus Graecus 1807 del siglo IX d.C., este diálogo se encuentra entre el Minos y el Epinomis. Si en elMinos el discípulo hace referencia a la diversidad de ritos y costumbres observables en los diferentes pueblos, en el Epinomis se hace énfasis en la unidad de la ley. La regulación del simposio, del acceso a los fármacos, a las bebidas embriagantes y a los medicamentos, es un tema fundamental en las Leyes, lo que es visible por la composición misma del diálogo, pues es en los primeros libros donde se trata esta temática. El arte de regular la vida en comunidad se muestra como una técnica perfectible a través del diálogo. Las bebidas en común pueden ser benéficas, dice el anónimo extranjero Ateniense, pues el vino anima a los ciudadanos a cantar y a través de la confrontación con el placer los ciudadanos ejercitan la templanza. Como el consumo de vino también puede producir excesos y desmesuras debe regularse su consumo. El Ateniense propone un límite mínimo de edad para beber vino que es de 18 años (Leyes 2.666a-e). La postura del extranjero Ateniense, en cuanto al tema de la regulación de los fármacos, es un mensaje que podríamos catalogar como “antiprohibicionista”, si bien no en el sentido contemporáneo, individualista y liberal, sí en el sentido en que no se propone prohibir a los ciudadanos los fármacos de manera absoluta: se propone permitirlos, pero bajo una estricta regulación legal y comunitaria.
The Regulation of Drugs in Plato’s Laws
Keywords: Plato; Laws; Philosophy of Right; Drug regulation; Platón; Leyes; Filosofía del derecho; Regulación de los fármacos; https://purl.org/pe-repo/ocde/ford#6.03.01